GOOD CORPORATE GOVERNANCE IMPLEMENTATION AS A PERFORMANCE AND COMPANY VALUE - Samari, Wahyu (Dinasti International Journal of Economics, Finance & Accounting, 2020)
Good corporate governance or commonly called as GCG can be said as a tool for control of corporate decision making that is fair and accountable. So that the decision taken by the company management has considered all interested parties such as shareholders, board of commissioners, board of directors in their efforts to improve the performance and value of the company while also considering other stakeholders. Understanding GCG does not have the same definition but has almost the same spirit and values. The emphasis of GCG is on the necessity of a commitment to apply the rules of the game and to conduct business in a healthy and ethical manner. At present, where information disclosure and advancement of knowledge in all fields are advancing rapidly, encouraging capital owners and company managers to innovate and be creative in conducting their business. This condition 'forces' the company to compete as a winner in getting the maximum profit and sometimes causes problems both within the company and outside the company. A good GCG implementation will suppress problems that might arise such as bribery, corruption, investment fraud, embezzlement of funds, abuse of authority, environmental pollution, etc.